Real Exchange Rate Volatility and the Price of Nontradables in Sudden-Stop-Prone Economies - Mendoza, Enrique (IMF Working Papers; Working Paper ;, 2006)
This paper shows that the dominant view that the high variability of real exchange rates is due to movements in exchange rate-adjusted prices of tradable goods does not hold for Mexican data for periods with a managed exchange rate. The relative price of nontradables accounts for up to 70 percent of real exchange rate variability during these periods. The paper also proposes a model in which this fact, and the sudden stops that accompanied the collapse of Mexico's managed exchange rates, could result from a Fisherian debt-deflation mechanism operating via nontradables prices in economies with dollarized liabilities.